Comparison of an Energy-Reduced Mediterranean Diet and Physical Activity Versus an Ad Libitum Mediterranean Diet in the Prevention of Type 2 Diabetes. - Ruiz-Canela, Miguel; Corella, Dolores; Martínez González, Miguel Ángel; Babio, Nancy; Martínez, J. Alfredo; Forga, Luis; Alonso-Gómez, Ángel M.; Warnberg, Julia; Vioque, Jesús; Romaguera, Dora; López-Miranda, José; Estruch, Ramón; et al. (American College of Physicians (ACP), 2025)
Prespecified secondary outcome analysis in the PREDIMED (Prevención con Dieta Mediterránea) Plus randomized, single-blinded, controlled trial. (ISRCTN Registry: ISRCTN89898870) Setting: 23 centers across Spain. Participants: 4746 adults aged 55 to 75 years with metabolic syndrome and overweight or obesity, without prior cardiovascular disease or diabetes. Participants were randomly assigned 1:1 to an intervention group receiving an erMedDiet (planned reduction of 600 kcal per day), increased physical activity, and behavioral strategies for reducing weight, or a control group receiving ad libitum MedDiet advice. Results: During the 6-year intervention period, absolute risk was 12.8% (95% CI, 11.0% to 14.5%) in the control group and 10.3% (CI, 8.8% to 11.8%) in the intervention group; the absolute risk reduction was 2.5% (CI, 4.7% to 0.3%); and the adjusted Hazard ratio was 0.67 (CI, 0.56 to 0.80). When the extended follow-up period beyond the intervention period (range between more than 6 years and 8.6 years) was included, diabetes incidence was 31% (CI, 18% to 41%) relatively lower in the intervention group (280 cases) compared with the control group (349 cases). Limitation: Secondary outcome, single-blinded design, and self-reported dietary adherence. Conclusion: An intensive intervention with the MedDiet adding caloric reduction, physical activity, and modest weight loss was more effective than only an ad libitum MedDiet in reducing diabetes incidence in overweight/ obese persons with metabolic syndrome
Keywords: Medicina preventiva; Diabetes tipo 2 - Prevención; Alimentación - Mediterráneo (Región); PREDIMED; Mediterranean diet; Dietary adherence; Prevention of Type 2 Diabetes